1988
DOI: 10.1143/jjap.27.l2248
|View full text |Cite
|
Sign up to set email alerts
|

New Amorphous Mg-Ce-Ni Alloys with High Strength and Good Ductility

Abstract: New Mg-based amorphous alloys with high strength and good ductility were produced in the Mg-Ce-Ni system by melt spinning. The tensile fracture strength ( σf) and Vickers hardness reach 750 MPa and 199 DPN for Mg80Ce10Ni10. The specific strength defined by the ratio of σf to density is as high as 27, being considerably higher than the highest value (≃20) for conventional Al-based alloys. The high-strength Mg-base amorphous alloys are expected to attract much attention as a new type of high-strength material w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
207
1
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 533 publications
(214 citation statements)
references
References 11 publications
5
207
1
1
Order By: Relevance
“…The high glass-forming ability enables us to prepare bulk glassy alloys by copper mold casting or quenching the melt in a quartz tube into stirred water. As a result, a number of bulk glassy alloys have been successfully prepared in multicomponent systems such as Mg-, 2) Zr-, 3) Ti-, 4) Fe-, 5) Pd-, 6) Ni-, 7) Co- 8) and based alloys. Summarizing the features of the above-mentioned multicomponent systems, the following three empirical rules have been proposed, 10) i.e., (1) multi-component systems consisting of more than three kinds of elements, (2) significant difference in atomic size ratios above 12% among the main constituent elements, and (3) suitable negative heats of mixing among their main elements.…”
Section: Introductionmentioning
confidence: 99%
“…The high glass-forming ability enables us to prepare bulk glassy alloys by copper mold casting or quenching the melt in a quartz tube into stirred water. As a result, a number of bulk glassy alloys have been successfully prepared in multicomponent systems such as Mg-, 2) Zr-, 3) Ti-, 4) Fe-, 5) Pd-, 6) Ni-, 7) Co- 8) and based alloys. Summarizing the features of the above-mentioned multicomponent systems, the following three empirical rules have been proposed, 10) i.e., (1) multi-component systems consisting of more than three kinds of elements, (2) significant difference in atomic size ratios above 12% among the main constituent elements, and (3) suitable negative heats of mixing among their main elements.…”
Section: Introductionmentioning
confidence: 99%
“…In some exceptional cases, heating amorphous alloys produces undercooled melt. [17][18][19][20][21][22][23][24] In the case of the Al 2 O 3 -Y 2 O 3 system, it is emphasized that the undercooled melt is produced by heating the metastable eutectic structure consisting of crystal phases. 16) Uniform Al 2 O 3 -YAG eutectic structure with sub-micron order in spacing was formed when solidification in the equilibrium path was accompanied by the melting of the metastable eutectic structure.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that a large supercooled liquid region is found in multicomponent systems for metallic alloy systems. [17][18][19][20][21][22][23][24] 28) This paper focuses on the eutectic selection and the undercooled melt formation in the Al 2 O 3 -Y 2 O 3 -ZrO 2 pseudo-ternary system. Firstly, criterion for selection of the eutectic systems is examined in terms of maximum melt temperature by using an optical DTA apparatus.…”
Section: Introductionmentioning
confidence: 99%
“…However, during the last decade, some exceptions have been reported because of the discoveries of stabilized supercooled liquid alloys without crystallization even during cooling at slow rates below 100 K/s [1,2]. As a result, bulk amorphous alloys have been prepared in a number of alloy systems such as Mg- [3], Ln(lanthanide)- [4], Zr- [5,6], Fe- [7], Pd-Cu- [8], Ti- [9], Ni- [10] and Co- [11] bases and have gained some applications due to their unique mechanical properties, chemical properties and good workability resulting from the amorphous structure. It has subsequently been found that the use of the stabilized liquid also gives rise to bulk amorphous alloys containing nanocrystalline [12] and nanoquasicrystalline [13] particles with good mechanical properties in the Zr-based alloy systems.…”
Section: Introductionmentioning
confidence: 99%